Small Molecules in Hematology (Recent Results in Cancer Research,, 2018)
This book, written by respected experts, discusses in detail the latest developments in targeted therapy for hematologic malignancies using small molecules. It covers a wide range of small molecules including tyrosine kinase inhibitors, immunomodulatory drugs, the IDH-2 inhibitor enasidenib, the BCL-2 inhibitor venetoclax, and the proteasome inhibitor carfilzomib. For each molecule, aspects such as the chemical structure, mechanism of action, drug targets, drug interactions, preclinical studies, clinical trials, treatment applications, and toxicity are discussed. Extensive research into the molecular mechanisms of cancer has heralded a new age of targeted therapy. The field of precision cancer therapy is now growing rapidly, and the advances being made will mean significant changes in the treatment algorithms for cancer patients. Numerous novel targets that are crucial for the survival of cancer cells can be attacked by small molecules such as protein tyrosine kinase inhibitors. An accompanying volume addresses the use of small molecules in oncology, and the two volumes together represent the third edition of the book originally published under the same title. .